Web-based dynamic similarity distance tool - Azmi, Mohd Sanusi; Draman @ Muda, Azah Kamilah; Draman @ Muda, Noor Azilah; Arbain, Nur Atikah; Radzid, Amirul Ramzani; Nordin, Radzuan (Penerbit Universiti, UTeM, 2018)
Similarity or distance measures is a well-known method and commonly used for calculating the distance between two samples of a dataset. Basically,the distance between the dataset samples is an important theory in multivariate analysis research. This paper proposes a tool that provides seven common distance methods that can be used in various research area. This tool is a web-based application which can be accessed through the internet browser. The objective of this tool is to introduce a web-based similarity distance application for many analysis and research purposes. Besides, a ranking method based on the Mean Average Precision is also implemented in this tool in order to increase the classification accuracies. This tool can process features that contain numerical values from any type of dataset.